PARP inhibitors: risk factors for toxicity and matching patients to the proper poly (ADP-ribose) polymerase inhibitor (PARPi) therapy. Issue 5 (27th January 2023) - Chelariu-Raicu, Anca; Trillsch, Fabian; Burges, Alexander; Czogalla, Bastian; Hester, Anna; Wuerstlein, Rahel; Harbeck, Nadia; Mahner, Sven
Abstract : The past 5 years have seen several fundamental advances in ovarian cancer, with important new insights towards novel therapeutic opportunities within the DNA repair pathway. With the incorporation of poly (ADP-ribose) polymerase inhibitors (PARPi) into maintenance treatment regimens, the management of short- and long-term adverse events are key clinical priorities. Currently, three different PARPi are clinically beneficial and have been approved for primary and recurrent ovarian cancer: olaparib, niraparib, and rucaparib. The duration of treatment with PARPi in patients with ovarian cancer varies; patients can receive treatment for up to 2 or 3 years in first-line setting, or continue treatment until unacceptable toxicity or progression occurs in recurrent disease. Despite their similar mechanisms of action, these three inhibitors have specific toxicity profiles, which may lead to dose interruptions or discontinuation of treatment. This review summarizes the current indications for PARPi, including their role in recurrent and first-line maintenance treatment for advanced ovarian cancer. We also outline dose modifications leading to treatment disruption and potential changes in quality of life after prolonged treatment. Finally, we highlight the patient groups most likely to benefit from each of the three different PARPi.